Estimates of first-generation women and girls with female genital mutilation in the European Union, Norway and Switzerland. (1st November 2016) - Van Baelen, Luk; Ortensi, Livia; Leye, Els
Abstract: Background: Female genital mutilation (FGM) is the practice of partial or total removal of female genitalia for non-medical reasons. The procedure has no known health benefits but can cause serious immediate and long-term obstetric, gynaecological and sexual health problems. Health workers in Europe are often unaware of the consequences of FGM and lack the knowledge to treat women adequately. Objective: Our goal was to estimate the number of first-generation girls and women in the European Union, Norway and Switzerland who have undergone FGM. Before migration from FGM-practicing countries began, FGM was an unknown phenomenon in Europe. Methods: Secondary analysis of data from the 2011 EU census and extrapolation from age-specific FGM prevalence rates in the immigrants' home countries to these data were used to provide our estimates. Estimates based on census and other demographic data were compared to our results for Belgium. Results: In 2011 over half a million first-generation women and girls in the EU, Norway and Switzerland had undergone FGM before immigration. One in two was living in the UK or France, one in two was born in East-Africa. Conclusions: For the first time, scientific evidence gives a reliable estimate of the number of first-generation women and girls in Europe coming from countries where FGM is practiced. The use of census data proves reliable for policy makers to guide their actions, e.g., regarding training needs for health workers who might be confronted with women who have undergone FGM, or the need for reconstructive surgery.